Possible bi-directional link between ETA receptors and protein kinase C in rat blood vessels - A. M. Northover; B. J. Northover (Mediators of Inflammation)
Possible links have been investigated between activation of protein kinase C (PKC) and endothelin (ET) production by small blood vessels. Perfusion pressures were recorded from rat isolated mesenteric artery, with or without the small intestine attached, before and after addition to the perfusate of either ET-1, ET-3 or the PKC activator 12-deoxyphorbol 13-phenylacetate (DOPPA). Rises in perfusion pressure in response to ET-1 (10−8 M)or DOPPA (10−6 M) were reduced significantly by pre-treatment with either the ETA receptor antagonist PD151242 (10−6 M) or the PKC inhibitor Ro 31-8220 (10−6 M). ET-3 (10−8 M) had a significant, albeit small, effect only when the gut was still attached to the mesentery. Inthis latter preparation ET-1 and DOPPA increased the permeability of villi microvessels to colloidal carbon in the perfusate. This effect of DOPPA was reduced by pre-treatment with either PD151242 or Ro 31-8220, but the effects of ET-1 were reduced significantly only by Ro 31-8220. ET-3 (10−8 M) was without effect. The results suggest a possible bi-directional link between ETA receptors and PKC in the intestinal vasculature.